Handbook of hydrothermal technology - Byrappa, K. (William Andrew, 2013)
Quartz, zeolites, gemstones, perovskite type oxides, ferrite, carbon allotropes, complex coordinated compounds and many more -- all products now being produced using hydrothermal technology. Handbook of Hydrothermal Technology brings together the latest techniques in this rapidly advancing field in one volume. The handbook provides a single source for understanding how aqueous solvents or mineralizers work under temperature and pressure to dissolve and recrystallize normally insoluble materials, and decompose or recycle any waste material. The result, as the authors show in the book, is technologically the most efficient method in crystal growth, materials processing, and waste treatment. Get a close look at the hydrothermal synthesis of zeolites, fluorides, sulfides, tungstates, and molybdates, as well as native elements and simple oxides. Delving into the commercial production of various types, the authors clarify the effects of temperature, pressure, solvents, and various other chemical components on the hydrothermal processes.
Keywords: Crystallization.; Crystal growth.; elektronické knihy; electronic books